Symposium 1: Changing the rules of the game - experiences with Web 2.0 learning in higher education - Nicolajsen, Hanne Westh (Proceedings of the International Conference on Networked Learning, 2012)
The use of Web 2.0 as tools for social learning within higher education is not as widespread as expected, nor with the expected results within non-distance teaching programmes. The question is why? Many have argued that Web 2.0 tools have potentials to support learning in various ways. It has been argued, but also questioned, that the current generation of students are digital natives prepared to use new media for learning. At the same time critical voices argue that learning designs with high degrees of Web2.0 characteristics challenge the prevailing norms for learning within most teaching systems. This study investigates reasons why Web 2.0 is difficult to adopt in teaching by looking at reflected feedback from students participating in an experiment using Web 2.0 for social learning. The challenges investigated are derived by looking into 37 undergraduate students’ reflections on their experiences and engagement using Web 2.0 technologies for collaborative discussions. The Web 2.0 discussions were part of an elective course in E-learning at the fourth semester at humanistic informatics at Aalborg University Copenhagen. Aalborg University is a PBL (problem based learning) university. Despite the contextual implications on the actual learning design investigated, the conclusions drawn are of general interest to the networked learning community. The conclusions drawn are that Web 2.0 learning challenges current norms with regard to distribution of control and responsibilities impacting the communication genre, the authenticity, quality assurance and blurring of the existing border between university and private life. Social status is found to influence the interaction to a worrying degree. However, at the same time the interaction holds the potential to challenge student images if students demonstrate unknown resources. Building more rigid learning designs may reduce some of these challenges, but such design will reduce the Web 2.0 characteristics - lowering the student control, the demand to be critical, the authenticity, and motivational issues related to the social interaction.